Exploring the antibacterial potential of novel fenamate-based derivatives: insights from molecular docking studies - Mehihi, Abbas Abdulridha; Abdul Hussein, Shaker Awad; Mahmood Kubba, Ammar A. Razzak; Aswed, Abdul Sattar; Saeed, Ali Mohammad (Pharmakeftiki, 2025)
The rapid emergence of antibiotic-resistant bacteria poses a critical global health threat, highlighting the urgent need for novel antimicrobial agents. In this context, fenamate-based drugs (nonsteroidal anti-inflammatory compounds containing a fenamic acid scaffold) have recently gained attention as promising antibacterial candidates. These agents have demonstrated potent activity against a spectrum of pathogenic bacteria, including multidrug-resistant (MDR) strains. In the present study, several newly synthesized derivatives incorporating a fenamate moiety were evaluated for their antibacterial properties against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli and Pseudomonas aeruginosa by using the agar diffusion technique. Most of the fenamate derivatives exhibited notable antibacterial activity, particularly against E. coli. Compounds 1, 3, and 5 showed the highest inhibitory effects, with compound 3 demonstrating the most potent activity, effectively suppressing all tested bacterial strains at concentrations as low as 250 µg/mL. These findings underscore the therapeutic potential of fenamate-based compounds in combating antibiotic resistance. Their capacity to overcome MDR mechanisms, possible synergistic interactions with existing antibiotics, and additional immunomodulatory properties render them compelling candidates for further investigation as next-generation antimicrobial therapies.